STATISTICAL ASSESSMENT OF THE DEVELOPMENT PROCESSES OF THE TRANSPORT INFRASTRUCTURE OF THE REGION (ON THE EXAMPLE OF THE REPUBLIC OF KARAKALPAKSTAN) (World Economics and Finance Bulletin, 2025)
The article analyzes the current state of the transport infrastructure of the Republic of Karakalpakstan, identifies key problems of its development in the context of the transition to a modern market economy. The areas of state and regional support aimed at forming an effective transport network that contributes to increasing the competitiveness of the region are considered
Keywords: transport infrastructure; automobile transport; Engel coefficient